2003
DOI: 10.1097/01.meg.0000059110.41030.bc
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic balloon dilation of Crohnʼs strictures

Abstract: Colonoscopic balloon dilation of Crohn's strictures can achieve long-term clinical benefit in many patients. Repeat dilations are justified in initial non-responders. In this series, the procedure appears safe with low morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(5 citation statements)
references
References 14 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…They suggested that primary strictures might be treated in the same way as anastomotic strictures. Recently, Thomas-Gibson et al 12 reported on a large series of cases (59 patients), describing a long-term clinical benefit of 41 percent (at a mean follow-up of 29 months) with two perforations. In our study, the cumulative nonsurgical rates for the dilation strictures were 93 percent at 12 months, 65 percent at 36 months, 81 percent at 12 months, and 46 percent at 36 months, including lesions that were not related to the dilation location.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They suggested that primary strictures might be treated in the same way as anastomotic strictures. Recently, Thomas-Gibson et al 12 reported on a large series of cases (59 patients), describing a long-term clinical benefit of 41 percent (at a mean follow-up of 29 months) with two perforations. In our study, the cumulative nonsurgical rates for the dilation strictures were 93 percent at 12 months, 65 percent at 36 months, 81 percent at 12 months, and 46 percent at 36 months, including lesions that were not related to the dilation location.…”
Section: Discussionmentioning
confidence: 97%
“…[3][4][5][6][7][8] However, there are few data concerning the long-term results of this treatment for Crohn_s strictures. [9][10][11][12] We investigated the safety and long-term efficacy of endoscopic hydrostatic balloon dilation for intestinal strictures in Crohn_s disease in a retrospective series.…”
mentioning
confidence: 99%
“…Technical success was achieved in all patients (n = 37). Repeat dilation was required in 40.5% (n = 15) of patients (long-term efficacy: 59.5%), with a median balloon dilation of 16.5mm (range [10][11][12][13][14][15][16][17][18]. Technical success and improvement in obstructive symptoms were achieved in all patients without AEs.…”
Section: Non-anastomotic Stricturesmentioning
confidence: 95%
“…During long-term follow-up patients needing surgery at 1, 3 and 5 years varies form 13%-17%, 28%-42%, and 36%-42% respectively. Strictures recur following dilation, and re-dilation may be required in up to 20% and 50% by 1 and 5 years, respectively [1,14,15] . The best results following dilation are obtained when stricture length is < 4 cm, and for anastomotic strictures when compared to de novo strictures [1,12,16] .…”
Section: Introductionmentioning
confidence: 99%
“…For these strictures, ELS can offer a minimally invasive alternative to surgery[ 126 ]. Among the different available stent types, FCSEMSs and PCSEMSs were used for this indication[ 128 , 129 ]. Preliminary experience has shown conflicting results with several studies reporting different clinical success rates that range between 36% to 100%.…”
Section: Common Applications and Complications Of Elsmentioning
confidence: 99%